Peranan Setiausaha Peperiksaan Dalam Amalan Pengurusan Peperiksaan di Maktab Perguruan dari Persepsi Pensyarah - Osman, Mohd Ali (1996)
This study propose to investigate the perceptions of lectures towards the practice of examination management by the Examination Secretaries of teacher training colleges from the aspects of planning, organizing, leadership and controlling. Demographic factors of respondents Including sex, race, post acquired, age and tine period knowing the Examination Secretary actioning as a moderating variable and is used to identify whether there is a significant difference on the practice of examination management. This study involved 301 respondents from 15 teacher training colleges in Kedah, Pulau Pinang, Perak, Wilayah Persekutuan Kuala Lumpur, Selangor, Kelantan and Terengganu. 420 sets of questionnaire were distributed by the researcher to the respondents. From those, only 381 responded and fully answered. The set of questionnaire consists of 50 item using five Likert scale. The data collected was analysed by using descriptive and inferency statistical method. Six main hypothesis were formed, tested using t-test, One-Way Analysis of Variance (A-NOVA), Pearson Correlation Analysis and Multiple Regression Analysis. The result of the research shows that there is a significant relationship and influences the planning, organising, leadership and controlling with the practice of examination management by the Examination Secretary of teacher training colleges. Leadership aspect has the dominant influences followed by the controlling aspects, organizing and planning. The result of the research too shows that there is significant different perception of respondents towards management practice of the examination based on age and post acquired. Besides, there is no significant difference of perception among respondents towards the practice management of examination based on sex, race and period known to the Examination Secretary. Various recommendations is drawn to increase the examination in teacher training colleges.